พฤติกรรมการป้องกันโรคเอดส์และปัจจัยที่เกี่ยวข้องของหญิงบริการทางเพศ จังหวัดเพชรบูรณ์ ปี พ.ศ. 2546 - โชษิตา คุ้มตลอด (จุฬาลงกรณ์มหาวิทยาลัย, 2003)
This is the analytic cross-sectional study with the objectives to assess AIDS preventive behavior and related factors: predisposing factors: enabling factors and reinforcing factors in female prostitutes in Phetchabun province. The studies populations were 453 female prostitutes in Phetchabun, whose names appeared in roster of AIDS and venereal disease control unit, Phetchabun provincial health office in January 2003. These female prostitutes were interviewed using the constructed questionnaire during December 2003 to February 2004. The results showed that 82.6% of female prostitutes in Phetchabun province had good level of AIDS preventive behavior. Predisposing factors which were significantly related to preventive behavior were age, education level, individual and family income, marital status, duration of working as female prostitute, knowledge and attitude of AIDS (P-value<0.05). Enabling factors which were significantly related to preventive behavior were employers support and convenience in care of health officer (P-value <0.001). Reinforcing factors which were significantly related to preventive behavior were advice from colleagues, the health officer s consulting and their regular physical check up (P-value <0.001). The results of this study may be used as the information for consideration of effective public health intervention in order to control and prevent of AIDS transmission among female prostitutes in Thailand.